Religiousity of Rural Moslem Women after Covid-19 - Ulya, Ulya; Farihah, Irzum; Amaliyah, Efa Ida (PALASTREN: Jurnal Studi Gender, 2023)
This study aims to gain women's perceptions about Corona or COVID 19 and the factors building their perceptions, as well as its influence on their religiosity after pandemic. This study is a qualitative research. The informants of this study were moslem women in Ngembal Kulon Village who were purposively selected based on their diverse educational and professional backgrounds. Observation and interview were used to collect the data. After all data were confirmed to be correct through triangulation, the data were analyzed through data reduction, data classification, data display, and conclusion or verification. The results show that moslem women in Ngembal Kulon understand Corona differently. Some of them understand it as a medical fact, as a theological fact, and as a political fact. These differences were caused by their respective pre-structures, namely the level and type of education, personal experience, sources of obtained information, and the environment. Then, it caused variousity to their personal responses towards COVID-19, responding to health protocols and vaccines. After pandemic, they actually felt an increase in religiosity: always maintaining health, obeying the government, and increasing spirituality.